Online Student Use of a Proximate Community of Engagement at an Independent Study Program - Oviatt, Darin R; Graham, Charles R.; Borup, Jered; Davies, Randall S (Online Learning, 2018)
Research has suggested that independent study students may benefit from engaging with a proximate community of engagement (PCE) while completing an online course and that they perceive that such engagement will help them succeed. Independent Study students were surveyed at the completion of their course to assess the level at which they actually interacted with a PCE. Survey findings were confirmed with follow-up interviews with students and their parents to triangulate survey data. Findings revealed that students in the study interacted with a PCE when completing the course. The percentage of students actually engaging with a PCE was lower than the percentages of students from a previous study who perceived that such engagement would be helpful. The research suggests that students made aware of the benefits of a PCE at the beginning of the course, and who receive coaching to curate that community as an assignment in the course, will be more likely to receive the learning benefits of community engagement. Future research to confirm the value of engaging with a proximate community, identifying most helpful and effective interactions, and helping students curate such a community were proposed. Keywords: Independent study, adolescent, online courses, online community, adolescent community of engagement, proximate community of engagement